Kinetics of the grating formation in holographic polymer-dispersed liquid crystals: NMR measurement of diffusion coefficients - Tang, Mingxue; Redler, Andreas; Topgaard, Daniel; Schmidt, Claudia; Kitzerow, Heinz-Siegfried (Colloid and Polymer Science)
Keywords: Materials Chemistry; Colloid and Surface Chemistry; Polymers and Plastics; Physical and Theoretical Chemistry

Effect of shear on vesicle and lamellar phases of DDAB/lecithin ternary systems - Youssry, Mohamed; Coppola, Luigi; Nicotera, Isabella; Ar, Gönül; Schmidt, Claudia (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

Molecular Recognition with 2,4-Diaminotriazine-Functionalized Colloids - Bayer, Frank M.; Tang, Mingxue; Michels, Rolf; Schmidt, Claudia; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Homogeneous length scale of shear-induced multilamellar vesicles studied by diffusion NMR - Åslund, Ingrid; Medronho, Bruno; Topgaard, Daniel; Söderman, Olle; Schmidt, Claudia (Journal of Magnetic Resonance)

Planar lamellae and onions: a spatially resolved rheo–NMR approach to the shear-induced structural transformations in a surfactant model system - Medronho, Bruno; Brown, Jennifer; Miguel, Maria Graça; Schmidt, Claudia; Olsson, Ulf; Galvosas, Petrik (Soft Matter)
Keywords: Condensed Matter Physics; General Chemistry

Novel drug delivery systems: Chitosan conjugates covalently attached to steroids with potential anticancer and agrochemical activity - Pérez Quiñones, Javier; Szopko, Richard; Schmidt, Claudia; Peniche Covas, Carlos (Carbohydrate Polymers)
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry

Size Determination of Shear-Induced Multilamellar Vesicles by Rheo-NMR Spectroscopy - Medronho, B.; Schmidt, Claudia; Olsson, U.; Miguel, M. G. (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Shear-Induced Defect Formation in a Nonionic Lamellar Phase - Medronho, B.; Rodrigues, M.; Miguel, M. G.; Olsson, U.; Schmidt, Claudia (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Manifestation of Berry’s Phase in Nuclear Quadrupole Resonance Spectra of Rotating Powder Samples - Sinyavsky, Nikolay; Maćkowiak, Mariusz; Schmidt, Claudia (Zeitschrift für Naturforschung A)
The effect of Berry’s phase on the nuclear quadrupole resonance (NQR) spectra of rotating powder samples is studied experimentally, and its application for the determination of the electric field gradient asymmetry η is demonstrated. The NQR frequency splittings, which are observed for the spin 3/2 nucleus of 35 Cl in powder samples of p-dichlorobenzene (C 6 H 4 Cl 2 ) and cyanuric chloride (C 3 N 3 Cl 3 ), are interpreted as a manifestation of Berry’s phase, associated with the adiabatically changing Hamiltonian due to sample rotation. The accumulation of Berry’s phase during the rotation process is responsible for the observed dependence of the NQR line shape on the rotation frequency and the asymmetry parameter. The proposed method for the determination of η involves the analysis of the NQR powder patterns of the rotating samples.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy; Mathematical Physics

Shear-Induced Transitions between a Planar Lamellar Phase and Multilamellar Vesicles: Continuous versus Discontinuous Transformation - Medronho, B.; Shafaei, S.; Szopko, R.; Miguel, M. G.; Olsson, U.; Schmidt, Claudia (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Rheo-NMR Spectroscopy - Schmidt, Claudia (Modern Magnetic Resonance)

Director Orientation of Nematic Side-Chain Liquid Crystalline Polymers Under Shear Flow: Comparison of a Flow-Aligning and a Non-Flow-Aligning Polysiloxane - Siebert, Hartmut; Quijada-Garrido, Isabel; Vermant, Jan; Noirez, Laurence; Burghardt, Wesley R.; Schmidt, Claudia (Macromolecular Chemistry and Physics)
Keywords: Materials Chemistry; Organic Chemistry; Polymers and Plastics; Physical and Theoretical Chemistry; Condensed Matter Physics

Coexisting lamellar phases in water–oil–surfactant systems induced by the addition of an amphiphilic block copolymer - Frank, Christian; Strey, Reinhard; Schmidt, Claudia; Stubenrauch, Cosima (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

Lyotropic Lamellar Polysiloxanes with Isomeric Amphiphilic Side Chains - Burgemeister, Daniel; Farrell, Tony; Schmidt, Claudia (Macromolecular Chemistry and Physics)
Keywords: Materials Chemistry; Organic Chemistry; Polymers and Plastics; Physical and Theoretical Chemistry; Condensed Matter Physics

Lamellar Liquid Single Crystal Hydrogels: Synthesis and Investigation of Anisotropic Water Diffusion and Swelling - Kleinschmidt, Felix; Hickl, Markus; Saalwächter, Kay; Schmidt, Claudia; Finkelmann, Heino (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Shear-Induced Order in Nematic Polymers - Becker, Patrick; Siebert, Hartmut; Noirez, Laurence; Schmidt, Claudia (Macromolecular Symposia)
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry; Condensed Matter Physics

Director reorientation of a side-chain liquid crystalline polymer under extensional flow - Cormier, Ryan J.; Schmidt, Claudia; Callaghan, Paul T. (Journal of Rheology)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

A new approach to lamellar phases (Lα) in water – non-ionic surfactant systems - Stubenrauch, C.; Burauer, S.; Strey, R.; Schmidt, Claudia (Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Deuterium NMR Study of Slow Relaxation Dynamics in a Polymer-like Micelles System after Flow-Induced Orientation - Angelico, R.; Burgemeister, D.; Ceglie, A.; Olsson, U.; Palazzo, G.; Schmidt, Claudia (The Journal of Physical Chemistry B)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Physical and Theoretical Chemistry

Phase Behavior of n-Alkyl-substituted Polysilanes - Mueller, Christian; Peter, Christine; Frey1, Holger; Schmidt, Claudia (Silicon Chemistry)